“Comrade! What Have You Done for Western Front?”: Participation of Inhabitants of Siberia in Collecting Donations for Benefit of Workers’ and Peasants’ Red Army (1920) - K. A. Tishkina (Научный диалог)
Using the example of Siberia, the implementation of collection activities in support of the Workers’ and Peasants’ Red Army (RKKA) on the Western Front is examined in the article. Attention is drawn to the fact that the initiative to carry out such actions came from the country’s leadership and the party apparatus. The main stages of preparation and holding of the “Week of Help to the Western Front” both in cities and in the countryside of Siberia in the summer and autumn of 1920 are investigated in detail. The relevance of the study is due to both the appeal to the topic of the Soviet-Polish war as a whole, and the reconstruction of the general picture of the situation in Siberian society after the establishment of Soviet power. Based on the involvement of a wide range of sources, the main forms of collecting donations have been identified: deductions from wages; transfer of funds from the sale of tickets for performances and concerts, reception of things and products, etc. It is concluded that the conduct of fundraising campaigns for the needs of the Red Army in Siberia had a wide practice and took place in difficult economic conditions associated with the recently ended Civil War and food appropriation.